1975
DOI: 10.1104/pp.55.2.414
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Nutrition and Starch Metabolism in Phaseolus vulgaris L.

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

1977
1977
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 15 publications
(15 reference statements)
0
16
0
Order By: Relevance
“…The carbohydrate content increased with increasing edaphic and foliar doses, showing that zinc increases the carbohydrate content in cowpea beans, and the 0.250 g edaphic-50.0 mM foliar dose produced the highest carbohydrate content. Many zinc-dependent enzymes are involved in carbohydrate metabolism, so zinc is involved in starch formation [47]. Protein contents between 25.27 and 29.58% were found, which were higher than the 23.90% protein reported for cowpea beans [36] and the control (0.0 g edaphic-0.0 mM foliar).…”
Section: Physicochemical Compositionmentioning
confidence: 72%
“…The carbohydrate content increased with increasing edaphic and foliar doses, showing that zinc increases the carbohydrate content in cowpea beans, and the 0.250 g edaphic-50.0 mM foliar dose produced the highest carbohydrate content. Many zinc-dependent enzymes are involved in carbohydrate metabolism, so zinc is involved in starch formation [47]. Protein contents between 25.27 and 29.58% were found, which were higher than the 23.90% protein reported for cowpea beans [36] and the control (0.0 g edaphic-0.0 mM foliar).…”
Section: Physicochemical Compositionmentioning
confidence: 72%
“…Zinc is required in the synthesis of tryptophan, which is a precursor of indole-3-acetic acid (Oosterhuis et al 1991), a hormone that inhibits abscission of squares and bolls. This nutrient also has a favourable eect on the photosynthetic activity of leaves and plant metabolism (Jyung et al 1975), which might account for higher accumulation of metabolites in reproductive organs (bolls). Results obtained are con®rmed by those of Zeng QingFang (1996).…”
Section: Resultsmentioning
confidence: 99%
“…This correlation reflects the energy value of barley for both malting and feeding. Reed (1940), Jyung et al (1975), and Sukhija et al (1987) reported the starch formation reduction under zinc deficiency in some crops. In this investigation, various amounts of starch content increase were obtained by zinc applications.…”
Section: Resultsmentioning
confidence: 99%